Discordance between germline genetic findings and abnormal tumor immunohistochemistry staining of mismatch repair proteins in individuals with suspected Lynch syndrome - Pan, Shujuan; Cox, Hannah; Willmott, Jamie; Mundt, Erin; Gorringe, Heidi; Landon, Michelle; Bowles, Karla R.; Coffee, Bradford; Roa, Benjamin B.; Mancini-DiNardo, Debora (Frontiers in Oncology, 2023)
Background and Aims: Tumor immunohistochemical staining (IHC) of DNA mismatch repair (MMR) proteins is often used to guide germline genetic testing and variant classification for patients with suspected Lynch syndrome. This analysis examined the spectrum of germline findings in a cohort of individuals showing abnormal tumor IHC. Methods: We assessed individuals with reported abnormal IHC findings and referred for testing with a six-gene syndrome-specific panel (n=703). Pathogenic variants (PVs) and variants of uncertain significance (VUS) in MMR genes were designated expected/unexpected relative to IHC results. Results: The PV positive rate was 23.2% (163/703; 95% confidence interval [CI], 20.1%-26.5%); 8.0% (13/163; 95% CI, 4.3%-13.3%) of PV carriers had a PV in an unexpected MMR gene. Overall, 121 individuals carried VUS in MMR genes expected to be mutated based on IHC results. Based on independent evidence, in 47.1% (57/121; 95% CI, 38.0%-56.4%) of these individuals the VUSs were later reclassified as benign and in 14.0% (17/121; 95% CI, 8.4%-21.5%) of these individuals the VUSs were reclassified as pathogenic. Conclusions: Among patients with abnormal IHC findings, IHC-guided single-gene genetic testing may miss 8% of individuals with Lynch syndrome. In addition, in patients with VUS identified in MMR genes predicted to be mutated by IHC, extreme caution must be taken when the IHC results are considered in variant classification.